2000
DOI: 10.1076/0271-3683(200008)21:2;1-v;ft608
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase activity is enhanced during corneal wound repair in high glucose condition

Abstract: MMP activity was enhanced in healing corneal epithelium, both in in vitro and in vivo diabetic models, suggesting its involvement in diabetic keratopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…This result is in line with other findings showing that MMP activity was higher in aortic homogenates and plasma in rat models of diabetes (25). High glucose levels have also been shown to raise MMP activity in cultured cells (25,26). Nevertheless, despite this raise in MMP content, the quantity of cleaved collagen, reflecting the proteolytic process, was reduced in diabetic animals.…”
Section: Discussionsupporting
confidence: 80%
“…This result is in line with other findings showing that MMP activity was higher in aortic homogenates and plasma in rat models of diabetes (25). High glucose levels have also been shown to raise MMP activity in cultured cells (25,26). Nevertheless, despite this raise in MMP content, the quantity of cleaved collagen, reflecting the proteolytic process, was reduced in diabetic animals.…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that glucose at concentrations up to 17.5 mM has stimulatory effects on human corneal epithelial cell migration, adhesion, and proliferation, but concentrations above 31 mM have an inhibitory effect. 34,35 To eliminate a possible competitive effect of glucose present in the culture medium with the effect of CMC on the HCLE cell migration, cell adhesion, and proliferation and scratch-wound closure, we included a control group of culture medium containing 12.5 mM glucose but with no CMC in all our assays.…”
Section: Iovsmentioning
confidence: 99%
“…There are many external cues which can induce various transcription factors (TFs) to act on the MMP‐9 promoter, though evidence linking the extracellular cues to the intracellular pathways is scarce. In cell culture models, MMP‐9 production has been shown to be regulated by external factors such as osmolarity shifts (Li et al, 2004), high glucose (Takahashi et al, 2000), plating density (Bargagna‐Mohan et al, 1999), phorbol esters (Fini et al, 1995), and several growth factors and cytokines including interleukin 1β (IL‐1β) (Li et al, 2001), tumor necrosis factor‐alpha (TNF‐α) (Li et al, 2001), transforming growth factor β (TGF‐β) (Li et al, 2001), basic fibroblast growth factor (FGF‐2) (Mohan et al, 2000), and platelet activating factor (PAF) (Tao et al, 1995). Additionally, hyaluronan and several sulfated GAGs have been shown to stimulate MMP‐9 in both dermal and corneal explants (Isnard et al, 2003).…”
mentioning
confidence: 99%